Tungsten‐Doped CoP Nanoneedle Arrays Grown on Carbon Cloth as Efficient Bifunctional Electrocatalysts for Overall Water Splitting. Issue 20 (16th October 2019) - Ren, Zhiguo; Ren, Xiaochuan; Zhang, Liao; Fu, Cehuang; Li, Xiaofang; Zhang, Yingxi; Gao, Biao; Yang, Lijun; Chu, Paul K.; Huo, Kaifu
Abstract: The development of efficient and inexpensive bifunctional electrocatalysts with high activity and durability for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are highly desirable but challenging. Herein, we report the design and preparation of tungsten‐doped cobalt phosphide nanoneedle arrays on conductive carbon cloth (W−CoP/CC) as highly efficient and stable HER and OER electrocatalysts for overall water splitting. The nanoneedle array provides enriched active sites and facilitates ion diffusion and the 3D conductive CC skeleton enables fast charge transport. Moreover, tungsten doping improves the water adsorption ability, optimizes the hydrogen adsorption energy, and increases the electrochemical active surface area thereby resulting in much improved HER and OER catalytic activity. The W−CoP/CC composite shows low overpotentials of 32 mV at a current density of 10 mA cm −2 in 0.5 M H2 SO4 electrolyte for HER and 77 and 252 mV in 1 M KOH solution for HER and OER, respectively, outperforming most previously reported metal phosphide electrocatalysts. The electrolyzer for overall water splitting with W−CoP/CC as both the anode and cathode achieves a stable current density of 10 mA cm −2 at a low cell voltage of 1.59 V with no obvious voltage change even after operation for 20 h. The results provide a new strategy to design and prepare high‐performance non‐noble metal phosphides for overall water splitting. Abstract : Nanoneedle in a haystack : Tungsten‐doped CoP nanoneedle arrays were fabricated on carbon cloth as highly efficient and stable bifunctional electrocatalysts for overall water splitting in an alkaline electrolyte.